Common oral conditions associated with post-radiotherapy patients in Africa - Uwaila Otakhoigbogie,; Emmanuel O. Amobi,; Nonso E. Onyia,; Aisosa J.Osadolor,; Obehi O. Osadolor, (Nepal Mediciti Medical Journal, 2024)
Radiotherapy involves the use of high-energy radiation to shrink and or kill cancer cells, thus preventing the cells from growing, dividing, and spreading. Oral conditions associated with radiotherapy can affect the quality of life of post- radiotherapy patients when symptoms are not managed or prevented. The effects of radiotherapy on oral tissues is dependent on the total radiotherapy dose, fractionation system used, radiotherapy volume, radiation techniques used, entire and daily doses of radiotherapy and location of the tumour. Age, poor oral hygiene status prior to radiotherapy, gender, alterations in salivary production, mucosal trauma and nutritional status of the patient are some factors associated with radiotherapy related oral manifestations . After searching PubMed, ScienceDirect, African journal online and Google scholar by two independent investigators. The aim of this article was to review the available studies on the prevalence and common oral conditions/manifestations associated with post-radiotherapy patients in Africa. The oral conditions or manifestations reported from Africa based studies are oral mucositis , xerostomia ,dysphagia, radiation-related dental caries, dermatitis, altered taste sensation and osteoradionecrosis of the mandible. Treatment options for oral mucositis include basic oral care, sodium bicarbonate mouthwash, cryotherapy , chlorhexidine mouthwash, mixed medication mouthwash, anti-inflammatory agents, anti-microbial agents, local anesthetics, analgesics and natural agents such as honey. Xerostomia (dry mouth) can affect speech , taste ,chewing, swallowing and quality of life. There is need for more research towards understanding the preventive and treatment interventions to improve quality of life of post-radiotherapy patients.